The Perception of Teacher Well-being and Its Implications on The Interest of UNIMED Biology Education Students to Become a Teacher - Angel Areysia; Cwisan Angeltri Zalukhu; Florensia Saulina Pardede; Indah Yanti Dongoran; Natalia Togatorop; Natalia Silalahi (PT. Global Research Collaboration, 2024)
This study aims to analyze the interest and perceptions of teacher welfare among 52 respondents. Quantitative analysis revealed that 69.2% of respondents are highly interested in becoming teachers, while 30.8% are moderately interested. These findings reflect a strong commitment from the younger generation toward the teaching profession, despite significant concerns about financial welfare. Qualitative analysis identified two main themes: financial welfare and personal motivation. Many respondents felt that the salary they receive is not proportional to the responsibilities they bear, while intrinsic motivation, such as a desire to contribute to education, serves as a major driving factor in choosing this career. This study aligns with previous findings emphasizing the importance of financial welfare in job satisfaction for teachers but also offers new insights by highlighting personal motivation as a decisive factor. The conclusion of this research suggests that greater attention to teachers' financial welfare is necessary to attract high-quality individuals to the teaching profession and to create a better learning environment. Recommendations for policymakers include increasing compensation and support for teachers while considering their intrinsic motivations.